2022
DOI: 10.1371/journal.pone.0279811
|View full text |Cite
|
Sign up to set email alerts
|

Physiological adaptations and myocellular stress in short-term, high-frequency blood flow restriction training: A scoping review

Abstract: Background High frequency (1–2 times per day) low-intensity blood flow restriction (BFR) training has been recommended as a prescription approach for short durations of time to maximize relevant physiological adaptations. However, some studies demonstrate negative physiological changes after short periods of high-frequency BFR training, including prolonged strength decline and muscle fiber atrophy. Objectives To provide a comprehensive overview of short-term, high-frequency blood flow restriction training, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…A recent scoping review of short-term, high frequency BFR training protocols have identified numerous limitations within the existing literature. The ADAPT study will help to address many of the knowledge gaps identified, including; 1) the lack of personalised pressure applications, 2) lack of females, 3) lack of studies using clinical populations, 4) potentially high numbers of under-powered study designs, 5) limited data regarding the proximal effects of BFR, and 6) the absence of data investigating hypoalgesia responses to high frequency [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review of short-term, high frequency BFR training protocols have identified numerous limitations within the existing literature. The ADAPT study will help to address many of the knowledge gaps identified, including; 1) the lack of personalised pressure applications, 2) lack of females, 3) lack of studies using clinical populations, 4) potentially high numbers of under-powered study designs, 5) limited data regarding the proximal effects of BFR, and 6) the absence of data investigating hypoalgesia responses to high frequency [ 59 ].…”
Section: Introductionmentioning
confidence: 99%